2013
DOI: 10.1177/0731684413477222
|View full text |Cite
|
Sign up to set email alerts
|

Seismic retrofitting of rectangular reinforced concrete columns using fiber composites for enhanced flexural strength

Abstract: This article introduces an improved method using fiber composites for seismic retrofitting of rectangular reinforced concrete columns with a large side aspect ratio. To retrofit an existing column, near-surface-mounted (NSM) glass fiber reinforced polymer (GFRP) bars were adopted to enhance flexural strength, and then the potential plastic hinge region was confined by carbon fiber reinforced polymer (CFRP) jackets and CFRP anchors to ensure a ductile behavior. To evaluate the effectiveness of the strengthening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Furthermore, it was observed that the combination of NSM bars with CFRP wrapping improves the overall seismic performance of the column remarkably. In another study, Li et al [66] proposed using NSM GFRP rebars and CFRP jackets and CFRP anchors in the potential plastic hinge region for strengthening RC columns with a large side aspect ratio. Four types of strengthening layouts were used.…”
Section: Nsm Bars With Frp Wrappingmentioning
confidence: 99%
“…Furthermore, it was observed that the combination of NSM bars with CFRP wrapping improves the overall seismic performance of the column remarkably. In another study, Li et al [66] proposed using NSM GFRP rebars and CFRP jackets and CFRP anchors in the potential plastic hinge region for strengthening RC columns with a large side aspect ratio. Four types of strengthening layouts were used.…”
Section: Nsm Bars With Frp Wrappingmentioning
confidence: 99%
“…Therefore, both the beam yielding deformation and the plastic deformation are key parameters. 10,13 Let us define the ratio of the two key parameters as a new factor , which is closely related to the unloading stiffness value. Therefore, equation ( 27) is proposed to predict the values of K 4 , including this new factor,…”
Section: Unloading Stiffnessmentioning
confidence: 99%
“…It has been reported that columns with high postyield stiffness have good recoverability and reparability. 12,13,14 As for the study of the stiffness and residual deformation of this type of FRP-RC composite beam, it is much needed but still lack now.…”
Section: Introductionmentioning
confidence: 99%
“…According to the best knowledge of the authors', reversed cyclic flexural behavior of RC members strengthened with longitudinal FRP reinforcement was studied for the first time by Ilki and Kumbasar [46]. More recently, Bournas and Triantafillou [47], Goksu et al [48], Fahmy and Wu [49], Vrettos et al [50], Li et al [51], Goksu et al [52] and Faustino and Chastre [53] also studied this type of behavior. However, in all cases, except the studies of Goksu et al [48,52], it is difficult to perceive the performance of the NSM FRP system and anchoring of NSM reinforcement into the footing in case of low strength concrete.…”
Section: Introductionmentioning
confidence: 99%